Dark Tourism as a Tourism and Culture Development Strategy in Indonesia - Wailmi, Khil; Mahmudin, Tono; Novedliani, Riztrya; Randi, Randi; Samaduri, Lutpi (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research aims to (1) determine the potential for tourism and dark tourism culture in Indonesia; (2) knowing the strategy for developing tourism and culture through dark tourism. This research uses descriptive qualitative research. The data sources used in this research were obtained from books, websites and literature related to dark tourism as a tourism and culture development strategy in Indonesia. The analysis used in this research is SWOT analysis. The results of this research show that (1) the development of the attraction of dark tourism in Indonesia has great potential. Indonesia has a lot of dark tourism with historical and cultural values that attract tourists; (2) strategies for developing tourism and culture through dark tourism include marketing planning for dark tourism as tourism and culture, creating a dark tourism concept, collaborating with tourism agencies and private parties to support dark tourism, and education and promotion of dark tourism programs.